Immunogenicity induced by biologicals in the treatment of psoriasis and psoriatic arthritis: View of the problem - T. V. Korotaeva (Современная ревматология)
The present-day views of the immunogenicity of biological agents (BAs) used to in the treatment of psoriasis and psoriatic arthritis are analyzed. The immunogenicity of these medicaments is noted to depend on their molecular structure, individual patient characteristics, and used treatment regimens. As this takes place, the primary structure of the drug and its posttranslation modifications during manufacture are key factors. It is pointed out that a number of antigenic structures may give rise to the body's BA antibodies – murine epitopes, idiotopes, and allotropes, neoantigens forming in the coupling area of hybrid proteins, nonlinear epitopes present in the aggregated preparations. BAs that tend to form large immune complexes with these antibodies are most immunogenic. The antibodies to most BAs, except drugs based on soluble tumor necrosis factor-α receptors (etanercept), are neutralizing, i.e. they affect the efficiency of therapy, particularly when used over a long period of time.The results of trials evaluating the impact of antibodies to BAs on their clinical value are considered. It is believed that immunogenicity is itself of great importance in respect to the occurrence of the escape phenomenon of a response to BA therapy and to its safety. Attention is drawn to immunogenicity diagnostic problems; at the same it is noted that none of the used laboratory diagnostic techniques can reveal individual BA antibody forms and isotypes. It is concluded that there is a need for further investigations to standardize optimal methods for diagnosing neutralizing antibodies, to elaborate criteria for predicting a response to therapy in terms of an immunogenicity factor, and to reveal pathogenetic mechanisms responsible for the production of antibodies to BAs. The design of novel medicaments with minimal immunogenicity will depend on whether these mechanisms are common to all drugs or specific.